2021
DOI: 10.28982/josam.1000962
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cranial nerve blockage in patients with chronic migraine resistant to first-line treatment

Abstract: How to cite: Evcili G, Yabalak A. Effects of cranial nerve blockage in patients with chronic migraine resistant to first-line treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
2
1
0
Order By: Relevance
“…5,6,8,10,11 In addition, while the effects of PNB on the frequency and severity of pain have been evaluated in studies, the number of studies evaluating the effect on the migraine disability score is limited. [4][5][6] We also perform PNB on migraine patients in our clinic, and in our previously published study, 12 in line with data in the literature, we found that it was an effective treatment option. In our clinic, we have sometimes stopped use of prophylactic medications before PNB in some patients.…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…5,6,8,10,11 In addition, while the effects of PNB on the frequency and severity of pain have been evaluated in studies, the number of studies evaluating the effect on the migraine disability score is limited. [4][5][6] We also perform PNB on migraine patients in our clinic, and in our previously published study, 12 in line with data in the literature, we found that it was an effective treatment option. In our clinic, we have sometimes stopped use of prophylactic medications before PNB in some patients.…”
Section: Introductionsupporting
confidence: 83%
“…We also perform PNB on migraine patients in our clinic, and in our previously published study, 12 in line with data in the literature, we found that it was an effective treatment option. In our clinic, we have sometimes stopped use of prophylactic medications before PNB in some patients.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation